2008
DOI: 10.1128/aem.01547-07
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Expression of a Functional Recombinant Ganoderma lucidium Immunomodulatory Protein by Bacillus subtilis and Lactococcus lactis

Abstract: Bacillus subtilis and Lactococcus lactis are ideal hosts for the production of extracellular heterologous proteins of major commercial importance. A recombinant gene for the novel Ganoderma lucidium immunomodulatory protein LZ-8, recombinant LZ-8, was designed encoding the same amino acid sequence but using the preferred codons for both strains and was synthesized by overlapping extension PCR. Using the signal peptide (SP) from subtilisin YaB (SP YaB ), recombinant LZ-8 was expressed extracellularly in Bacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Haak-Frendscho et al [12] showed that FIP-glu (LZ-8) could stimulate IL-2 expression in hPBLs. Furthermore, Yeh et al [13]. found that recombinant FIP-glu (LZ-8) could improve the IL-2/IL-4 ratio in hPBMCs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Haak-Frendscho et al [12] showed that FIP-glu (LZ-8) could stimulate IL-2 expression in hPBLs. Furthermore, Yeh et al [13]. found that recombinant FIP-glu (LZ-8) could improve the IL-2/IL-4 ratio in hPBMCs.…”
Section: Discussionmentioning
confidence: 98%
“…FIPs had the ability of induction of cytokines expression. Ling Zhi-8 (LZ-8) could stimulate interleukin (IL)-2, IL-8, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α production in the hPBLs and could modulate IL-2/IL-4 balance in the human peripheral blood mononuclear cells (hPBMCs) [12,13]. Recombinant FIP-gts could enhance the level of IL-2 induction in murine splenocytes [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, no obvious changes in the morphology of LZ-8 treated BV-2 cells were observed under light microscopy (Figure 1(c)), and the marker of activated microglia, Iba-1, was not evident, indicating that BV-2 cells were not activated by LZ-8 (Figure 1(d)) (Ito, Tanaka, Suzuki, Dembo, & Fukuuchi, 2001). Furthermore, while LZ-8 activates murine macrophages and spleen cells by enhancing transcriptional expression or production of TNF-α (Chang, Chien, Tong, & Sheu, 2007;Li, Wen, Liu, Zhou, & Chen, 2012;Yang et al, 2014;Yeh, Yeh, Hsu, Luo, & Lin, 2008), no such stimulatory effect on TNF-α production in BV-2 microglia was detected (data not shown). It is well established that microglia serve as the resident macrophages in the brain and spinal cord, but, based on results of the present study, murine BV-2 microglia and RAW264.7 macrophages do not appear to have the same cellular responses to LZ-8.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression levels were commonly low. For example, the yield of reFIP-fve in insect cells was only 6.25 mg l -1 ) and reLZ-8 generated in B. subtilis and L. lactis are 17.4 and 1.24 mg l -1 , respectively (Yeh et al 2008). Moreover, the recombinant FIPs in E. coli possess lower bioactivities than native proteins or FIPs from insect cells (Ko et al 1997;Jinn et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Later on, the two genes have been expressed in baculovirus-infected insect cells and the recombinant proteins exhibited higher bioactivities than the reFIPs produced in E. coli (Jinn et al 2006;Wu et al 2008). Moreover, the reLZ-8 expressed in Bacillus subtilis was shown to be more effective and bioactive than that in Lactococcus lactis (Yeh et al 2008). Nevertheless, the yield was usually low in those expression systems.…”
Section: Introductionmentioning
confidence: 96%